2018
DOI: 10.1021/acschemneuro.8b00027
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Mutant Huntingtin Protein Expression in Living Cells by a Newly Identified RNA CAG Binder

Abstract: Expanded CAG trinucleotide repeats in Huntington's disease (HD) are causative for neurotoxicity. The mutant CAG repeat RNA encodes neurotoxic polyglutamine proteins and can lead to a toxic gain of function by aberrantly recruiting RNA-binding proteins. One of these is the MID1 protein, which induces aberrant Huntingtin (HTT) protein translation upon binding. Here we have identified a set of CAG repeat binder candidates by in silico methods. One of those, furamidine, reduces the level of binding of HTT mRNA to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…There are three well-known neurodegenerative diseases worldwide, namely Alzheimer’s, Parkinson’s, and Huntington’s diseases ( Armstrong and Barker, 2001 ). One of the major causes of those three neurodegenerative diseases is regarded as the abnormal protein aggregation in neurons, including β-amyloid for the pathogenesis and progression of Alzheimer’s disease, α-synulein to form proteinaceous cytoplasmic Lewy bodies for Parkinson’s disease and the aggregate-prone huntingtin protein for Huntington’s disease ( Chen and Tully, 2018 ; Clark et al, 2018 ; Kreutzer and Nowick, 2018 ; Matthes et al, 2018 ; Zhan et al, 2018 ; Zhang et al, 2018 ). Besides, the activation of the NLRP3 inflammasome also serves as a vital factor for the onset and development of neurodegenerative diseases ( Ahmed et al, 2017 ; Fu et al, 2017 ; Li et al, 2017 ; Sarkar et al, 2017 ; Wu et al, 2017 ; Aminzadeh et al, 2018 ; Bai et al, 2018 ; Gong et al, 2018 ; Qi et al, 2018 ).…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%
“…There are three well-known neurodegenerative diseases worldwide, namely Alzheimer’s, Parkinson’s, and Huntington’s diseases ( Armstrong and Barker, 2001 ). One of the major causes of those three neurodegenerative diseases is regarded as the abnormal protein aggregation in neurons, including β-amyloid for the pathogenesis and progression of Alzheimer’s disease, α-synulein to form proteinaceous cytoplasmic Lewy bodies for Parkinson’s disease and the aggregate-prone huntingtin protein for Huntington’s disease ( Chen and Tully, 2018 ; Clark et al, 2018 ; Kreutzer and Nowick, 2018 ; Matthes et al, 2018 ; Zhan et al, 2018 ; Zhang et al, 2018 ). Besides, the activation of the NLRP3 inflammasome also serves as a vital factor for the onset and development of neurodegenerative diseases ( Ahmed et al, 2017 ; Fu et al, 2017 ; Li et al, 2017 ; Sarkar et al, 2017 ; Wu et al, 2017 ; Aminzadeh et al, 2018 ; Bai et al, 2018 ; Gong et al, 2018 ; Qi et al, 2018 ).…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%
“…Thus, due to the high risk of off-target effects, furamidine is not a good candidate as an anti-HD drug. Nevertheless, this study shows that small molecules that mask RNA-protein interactions may be active against the mutant HTT protein [29].…”
Section: Rna-targeting Strategiesmentioning
confidence: 75%
“…The link between these molecules induces aberrant HTT protein translation. Matthes et al [29] identified a set of CAG repeat binders, one of which, furamidine, reduced the binding of huntingtin mRNA to several RNA-binding proteins in vitro [29]. Moreover, furamidine also decreased HTT protein levels in an HD cell line model [29].…”
Section: Rna-targeting Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular Dynamics (MD) simulations significantly help to investigate RNA–ligand interactions [ 15 , 16 , 17 ], complementing experimental work [ 18 ]. MD can shed light on RNA’s structural adaptation/flexibility and molecular recognition [ 19 , 20 , 21 ] under realistic conditions of an ionic solution [ 22 ].…”
Section: Introductionmentioning
confidence: 99%